THE PHENOMENON OF THE KOREAN WAVE AS A POLITICAL FACTOR OF «SOFT POWER» OF THE REPUBLIC OF KOREA - V I Kim (RUDN Journal of Political Science, 2017)
The article is of an overview nature and is devoted to the phenomenon of the Korean wave. This term refers to the toolkit of “soft power”, which is gaining increasing importance in world political practice. The article reveals the basic factors that determine the success of the Republic of Korea’s foreign policy in building an attractive image of its country. The notion of a state rebranding associated with a suc-cessful modernization of the economy and the Westernization of culture is singled out.